Development of the Motor Control Unit for Electric Vehicle - LI Yun; ZHU Shiwu; WU Chundong; JIAO Mingliang; YU Jun (Kongzhi Yu Xinxi Jishu)
It introduces the structures and power module packages of 4 typical Si-IGBT motor control units, presents the current status of power control unit based on SiC technology, and summarizes the development trends of motor control unit.